Suspension and resumption of kidney transplant programmes during the COVID‐19 pandemic: perspectives from patients, caregivers and potential living donors – a qualitative study. (29th July 2020) - Guha, Chandana; Tong, Allison; Baumgart, Amanda; Scholes‐Robertson, Nicole; Isbel, Nicole; Kanellis, John; Campbell, Scott; Coates, Toby; Chadban, Steven
Summary: Many countries have suspended kidney transplantation programmes during the COVID‐19 pandemic because of concerns for patient safety and the shortage of healthcare resources. This study aimed to describe patient, family member and potential donor perspectives on the suspension and resumption of kidney transplant programmes due to COVID‐19. We conducted seven online focus groups involving 31 adult kidney transplant candidates ( n  = 22), caregivers ( n  = 4) and potential donors ( n  = 5). Transcripts were analysed thematically. We identified five themes: cascading disappointments and devastation (with subthemes of shattering hope, succumbing to defeat, regret and guilt); helplessness and vulnerability (fear of declining health, confronted by the threat of and change in dialysis, disconnected from health care, susceptibility to infective complications); stress from uncertainty (confusion from conflicting information, unable to forward plan), exacerbating burdens (incurring extra financial costs, intensifying caregiver responsibilities), and sustaining health through the delay (protecting eligibility, relying on social support, adapting to emerging modalities of care). During the suspension of kidney transplantation programmes, patients felt medically vulnerable because of declining health, susceptibility to infection and reduced access to care. There is a need to address health vulnerabilities, disappointment, uncertainty and additional burdens arising from the suspension of kidney transplantation programmes.